MOSQUITO COILS SMOKE INDUCED SERUM BIOCHEMICAL ALTERATION IN ALBINO RATS - ASHA AGARWAL,; MOHD JABBAR,; RUPALI KUMARI, (International Journal of Pharma and Bio Sciences, 2014)
Present study was undertaken to investigate the toxicological effects of allethrin based mortein and prallethrin based goodknight mosquito coil smoke on serum biochemical parameters viz. total protein, albumin, globulin, urea, creatinine in albino rats. Experimental rats were divided into three sets (I, II and III) contain five rats each. Control set – I was kept away from the mosquito coils smoke. Experimental set – II exposed to mortein mosquito coil smoke and experimental set-III was exposed to goodknight mosquito coil smoke for 8 hours (8 am – 4 pm) daily for 4 weeks. A significant decrease in serum total protein (P < 0.05), albumin (P < 0.05), globulin (P < 0.05) while, a significant increase in serum urea (P < 0.05) and creatinine (P < 0.05) after both the brands of mosquito coils smoke exposure in comparison to control rats.The effects of mosquito coils smoke exposure interfere with metabolic functions of vital organs and cause alterations in biochemical parameters in rats.